Co-production of biosurfactant and indigo using wild-type Acinetobacter sp. isolated from soil - 여찬서; Sudheer Pammidimarri D. V. N.; 최권영 (Biotechnology and Bioprocess Engineering, 2024)
In this research, we investigated a naturally occurring, non-genetically modifi ed strain of Acinetobacter sp., isolated from soil, which demonstrated the capability to produce both indigo and biosurfactant. During the screening, indole was used as the sole carbon source in M9 minimal medium. The strain exhibiting the most intense blue coloration was isolated and further analyzed. The blue dye extracted from the cell culture was confi rmed as indigo through LC/MS analysis, showing an m/z value of 263.5, and H-NMR analysis. In LB medium, the wild-type Acinetobacter sp. strain produced approximately 6.8 mg/L of indigo from 1 mM indole. However, in M9 minimal medium, the production yield signifi cantly increased to 45.5 mg/L. Notably, the isolated strain showed vigorous bubbling during growth, which could facilitate the transport of indole and indigo dye, both of which have low solubility, across cell membranes. Additionally, this strain was capable of degrading medium-chain C12 alkane effi ciently. The whole genome was fully sequenced and analyzed for genes concerning biosurfactant and alkane metabolisms. In conclusion, utilizing a wild-type strain for indigo production off ers a promising alternative to traditional chemical processes, addressing concerns related to genetically modifi ed organisms in future applications.
Keywords: Acinetobacter sp.; Indigo dye; Indole; Biosurfactant